Does retirement age impact mortality? - Erik Hernaes; Simen Markussen; John Piggott; Ola Vestad (University of Oslo, Department of Economics, 2012)
This paper studies the relationship between retirement and mortality, using a unique administrative data set covering the full population of Norway. We make use of a series of retirement policy changes in Norway, which reduced the retirement age for a group of workers but not for others. By employing a difference-in-differences framework based on monthly birth cohort and treatment group status we first establish that the early retirement program significantly reduced the retirement age - this remains true when we account for program substitution, for example into the disability pension. Using instrumental variables estimation we find that retirement age has no effect on mortality.
Keywords: H55; I10; J11; J26; 330; Retirement age; Mortality; Instrumental variables; Policy evaluation; Altersgrenze; Sterblichkeit; Wirkungsanalyse; Instrumentalvariablen-Schätzmethode; Norwegen